‘How would you define your sexuality?’ analyzing the questions asked in official asylum interviews with sexual minorities - Selim, Hedayat; Helenelund, Mia; Vanto, Johanna; Skrifvars, Jenny; Alvesalo-Kuusi, Anne; Pirjatanniemi, Elina; Korkman, Julia; Antfolk, Jan (Taylor & Francis, 2026)
Asylum applications lodged by sexual minorities are expected to continue increasing in the future. Asylum interviews should be conducted in a way that supports fair and accurate asylum decision-making. Yet, psychological research has identified shortcomings in current asylum interviewing techniques. In this study, we analyzed interview style, question type, and question content in 129 Finnish asylum cases based on sexual orientation. Officials mainly used the information-gathering style of interviewing and rarely used the most unrecommended (i.e. suggested and forced choice) question types (3%). However, only 12% of all questions were open questions, whereas focused and yes/no questions were predominant. Over half of all questions sought to establish the credibility of the applicants’ sexual orientation, whereas 29% of questions inquired about their accounts of persecution. To assess the credibility of sexual orientation, officials primarily asked about applicants’ relationships, their feelings, and their sexual identity development, reflecting Western understandings of human sexuality. Asking more open questions and focusing more extensively on assessing applicants’ persecution risk would improve current interviewing practice. To support fair and accurate asylum decision-making, future research should investigate how queer people worldwide experience their sexual identity development. Training programs could also support asylum officials in conducting interviews in this context.